2020
DOI: 10.1038/s41467-020-14378-x
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct temporal integration of noradrenaline signaling by astrocytic second messengers during vigilance

Abstract: Astrocytes may function as mediators of the impact of noradrenaline on neuronal function. Activation of glial α1-adrenergic receptors triggers rapid astrocytic Ca 2+ elevation and facilitates synaptic plasticity, while activation of β-adrenergic receptors elevates cAMP levels and modulates memory consolidation. However, the dynamics of these processes in behaving mice remain unexplored, as do the interactions between the distinct second messenger pathways. Here we simultaneously monitored astrocytic Ca 2+ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
143
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 56 publications
11
143
1
Order By: Relevance
“…Recent evidence indicates that depending on the vigilance states, astrocytes of the auditory cortex integrate NE activity through distinct signaling pathways. Thus, while transient NE release is accompanied with large cytosolic astrocytic Ca 2+ elevations, sustained activity of noradrenergic neurons leads to a gradual increase of cAMP (Oe et al, 2020). Our results strongly suggest that similar regulations occur in BGCs since β1-AR-mediated GluA1 phosphorylation induced by stimulant medications relies on sustained activity on LC NE neurons projecting to the cerebellum.…”
Section: Discussionsupporting
confidence: 56%
“…Recent evidence indicates that depending on the vigilance states, astrocytes of the auditory cortex integrate NE activity through distinct signaling pathways. Thus, while transient NE release is accompanied with large cytosolic astrocytic Ca 2+ elevations, sustained activity of noradrenergic neurons leads to a gradual increase of cAMP (Oe et al, 2020). Our results strongly suggest that similar regulations occur in BGCs since β1-AR-mediated GluA1 phosphorylation induced by stimulant medications relies on sustained activity on LC NE neurons projecting to the cerebellum.…”
Section: Discussionsupporting
confidence: 56%
“…Recent evidences highlight important roles of astroglia in regulating neural activity, brain states, and animal behavior, both in vertebrates (Brancaccio, Patton, Chesham, Maywood, & Hastings, 2017) and invertebrates (Ma, Stork, Bergles, & Freeman, 2016). Studies in rodents showed that astroglial cells are highly dynamic components of the brain, which respond to locomotion (Nimmerjahn, Mukamel, & Schnitzer, 2009; Sekiguchi et al, 2016; Slezak et al, 2019) or sensory stimulation (Gu et al, 2018; Slezak et al, 2019) with prominent changes in astroglial calcium levels and can regulate learning (Adamsky et al, 2018; Corkrum et al, 2020) or other state transitions (Bojarskaite et al, 2019; Cui et al, 2018; Oe et al, 2020; Poskanzer & Yuste, 2016) in the brain. Norepinephrine (Bekar, He, & Nedergaard, 2008; Oe et al, 2020; Salm & McCarthy, 1990; Shao & McCarthy, 1997) and acetylcholine (Araque, Martin, Perea, Arellano, & Buno, 2002; Pabst et al, 2016; Takata et al, 2011) are proposed to be the primary triggers for activating astroglia, yet several other molecules including glutamate (Hamilton et al, 2008; Mothet et al, 2005; Sun et al, 2013) play prominent roles in astroglial physiology.…”
Section: The Role Of Astroglia In Neural Circuit Function and Animalmentioning
confidence: 99%
“…Studies in rodents showed that astroglial cells are highly dynamic components of the brain, which respond to locomotion (Nimmerjahn, Mukamel, & Schnitzer, 2009; Sekiguchi et al, 2016; Slezak et al, 2019) or sensory stimulation (Gu et al, 2018; Slezak et al, 2019) with prominent changes in astroglial calcium levels and can regulate learning (Adamsky et al, 2018; Corkrum et al, 2020) or other state transitions (Bojarskaite et al, 2019; Cui et al, 2018; Oe et al, 2020; Poskanzer & Yuste, 2016) in the brain. Norepinephrine (Bekar, He, & Nedergaard, 2008; Oe et al, 2020; Salm & McCarthy, 1990; Shao & McCarthy, 1997) and acetylcholine (Araque, Martin, Perea, Arellano, & Buno, 2002; Pabst et al, 2016; Takata et al, 2011) are proposed to be the primary triggers for activating astroglia, yet several other molecules including glutamate (Hamilton et al, 2008; Mothet et al, 2005; Sun et al, 2013) play prominent roles in astroglial physiology. Consequently, activating astroglia triggers multiple cellular processes leading to release of gliotransmitters, such as glutamate (Fellin et al, 2004; Parpura et al, 1994; Parri, Gould, & Crunelli, 2001), adenosine triphosphate (ATP) (Newman, 2003; Pryazhnikov & Khiroug, 2008), D‐serine (Henneberger, Papouin, Oliet, & Rusakov, 2010) and GABA (Kozlov, Angulo, Audinat, & Charpak, 2006; Lee et al, 2010), which in turn alter neural activity.…”
Section: The Role Of Astroglia In Neural Circuit Function and Animalmentioning
confidence: 99%
“…A recent study has shown differential effects of NE on fear conditioning depending if the release of NE is long lasting or transient and could explain some of the discrepancies in fear-induced memory versus memory storage or spatial memory. Transient or bursting NE activity from a simple startle response elevated calcium levels in cortical astrocytes through activation of α 1 -ARs but prolonged NE activity during a head-fixed conditioned fear response elevated cAMP which was driven through activation of β-ARs ( Oe et al., 2020 ). This study would suggest that low vigilance or acute stress memories may be enhanced by α 1 -AR activation but high vigilance and chronic stress-induced memories such as fear conditioning is promoted mostly through β-AR activation.…”
Section: Conditioned Fear Memorymentioning
confidence: 99%